Determinants of long-term dual antiplatelet therapy use in post myocardial infarction patients: Insights from the TIGRIS registry. Issue 4 (April 2022) - Russo, Juan J; Yan, Andrew T; Pocock, Stuart J; Brieger, David; Owen, Ruth; Sundell, Karolina Andersson; Bagai, Akshay; Granger, Christopher B; Cohen, Mauricio G; Yasuda, Satoshi; Nicolau, Jose C; Brandrup-Wognsen, Gunnar; et al.
Highlights: Dual-antiplatelet therapy (DAPT) ≥1 year post myocardial infarction reduces major adverse cardiovascular events but increases bleeding. Appropriate patient selection for DAPT ≥1 year post myocardial infarction is important to avoid undue bleeding complications. In contemporary practice, DAPT use ≥1 year post myocardial infarction is prevalent and associated with patient and index event characteristics. There are marked geographical variations in DAPT use ≥1 year post myocardial infarction. Further clinical initiatives are needed to optimize patient selection for DAPT ≥1 year post myocardial infarction. Abstract: Background: Patterns of dual antiplatelet therapy (DAPT) use beyond 1 year post-myocardial infarction (MI) have not been well studied. Methods: TIGRIS (NCT01866904) was a prospective, multi-center (369 centers in 24 countries), observational study of patients 1 to 3 years post-MI. We sought to identify the prevalence and determinants of DAPT use ≥1 year post-MI in patients enrolled in TIGRIS. We used multivariable logistic regression to identify determinants of DAPT use at 396 days post-MI (365 days plus a 31day overrun period to account for intended DAPT discontinuation at 1 year). Patients treated with an oral anticoagulant were excluded. Results: Of 7708 patients (median age 67 years, women 25%, ST-elevation MI 50%), 39% and 16% were on DAPT at 396 days and 5 years post-MI, respectively. DAPT use at 396 days post-MI was more prevalent in patients <65 years of age, treated with percutaneous coronary intervention (versus coronary artery bypass grafting or medical therapy), and with multivessel disease or a history of angina. Additional clinical determinants of ischemic and/or bleeding events following MI (diabetes, second prior MI, hypertension, peripheral artery disease, heart failure, smoking, and renal insufficiency) were not independently associated with DAPT use at 396 days. There were geographic variations in the use of DAPT at 396 days ( p <0.001), with the lowest use in Europe and the highest in Asia and Australia. Conclusion: In a contemporary patient cohort, DAPT use beyond 1 year post MI was prevalent and associated with patient and index event characteristics. There were marked geographical variations in DAPT use beyond 1 year post MI. Graphical abstract: Image, graphical abstract